Nutritional Assessment and Disease Activity for Patients with Inflammatory Bowel Disease - Thomas E Wasser; James F Reed; Kathleen Moser; Pamela Robson; Linda Faust; Lori L Fink; Denise Wunderler (Canadian Journal of Gastroenterology)
Using the Harvard/Willett Semi-Quantitative Food Frequency Questionnaire (H/WSQFFQ), nutritional information was gathered on patients enrolled in an inflammatory bowel disease (IBD) registry. The registry lists 320 patients positive for either ulcerative colitis (n=124) or Crohn’s disease (n=196). The sample was limited to those 19 to 84 years old (mean ± SD 48.57±14.98), and comprised 136 males and 184 females. Using a battery of indices, quality of life, disease activity and general well-being were also assessed. Nutritional intake values from the Harvard-Willett data were compared with recommended dietary allowances (RDA) tables by sex and age group (19 to 24 years, 25 to 50, 51 and older) to discover any intake deficiencies. Results showed that IBD patients were below RDA guidelines for vitamin E, calcium, magnesium, zinc, iodine and selenium. Females were below RDA guidelines for iron while men were below for vitamin B6. There were also some deficiencies according to age in males and two nutrient deficiencies were seen by age group in women. There were no deficiencies by sex or age for vitamins A, C, D and niacin. There were no observed nutrient intake differences between ulcerative colitis and Crohn’s disease groups. Patients receiving vitamin or mineral supplementation showed significant decreases in quality of life, regardless of diagnosis (Crohn’s disease or ulcerative colitis) group. The H/WSQFFQ is a useful tool for assessment of the nutritional status of the IBD patient because it not only provides valuable measurement data to the clinician, but also adds to patient awareness about nutritional problems associated with IBD.